Linear Algebra, Vector Algebra and Analytical Geometry textbook - Konev, V. V. mathematician Associate Professor of Tomsk Polytechnic University, Candidate of Physics and Mathematics 1951- (TPU Publishing House, 2020)
This textbook consists of 3 parts devoted to the mathematical methods of Linear Algebra and Analytical Geometry based on the vector analysis technique. The basic concepts are explained by examples and illustrated by figures. The textbook is helpful for students who want to understand and be able to use matrix operations, solve systems of linear equations, analyze relative positions of figures, transform coordinate systems, and so on. The textbook is designed to foreign students of Tomsk Polytechnic University.